Altered expression of microRNA-30a-3p in papillary thyroid cancer and its association with clinicopathological characteristics - Todorović, Lidija; Mandušić, Vesna; Vučetić Tadić, Biljana; Živaljević, Vladan; Paunović, Ivan; Stanojević, Boban (Archives of Biological Sciences, 2020)
Paper description: Identification of novel molecular biomarkers can aid in stratification of patients with papillary thyroid cancer (PTC) into low- and high-risk prognostic groups. A growing body of evidence suggests a role for microRNA-30a-3p in aggressiveness and progression of various types of cancer. We show that miR-30a-3p expression levels were deregulated in PTC compared to non-tumor thyroid tissues. Decreased expression was associated with advanced stage, multifocality and capsular invasion. This is one of few studies of microRNA-30a-3p expression in PTC, indicating its potential involvement in the development and/or progression of this type of cancer. Abstract: A growing number of studies suggest a tumor suppressive role and potential prognostic significance of miR-30a-3p in different types of cancer. However, relatively few studies have focused on this microRNA in neoplastic thyroid lesions, including papillary thyroid cancer (PTC). The aim of our study was to shed more light on the potential involvement and clinical relevance of miR-30a-3p in this type of cancer. We examined the expression levels of this microRNA in 42 pairs of PTCs and matched non-tumor thyroid tissues using quantitative RT-PCR. We analyzed their association with clinical and histopathological parameters. The results revealed that miR-30a-3p was significantly downregulated in the majority of PTC tissues compared to corresponding non-tumor tissues. Moreover, decreased expression of miR-30a-3p was associated with advanced clinical stage, presence of multiple tumor foci and capsular invasion, suggesting a role in aggressive disease. Although the role of this microRNA and its prognostic utility remain to be elucidated, the presented data suggest that downregulated expression of miR-30a-3p indicates poorer prognosis in PTC patients, warranting further investigations. https://doi.org/10.2298/ABS191004063T Received: October 4, 2019; Revised: October 14, 2019; Accepted: October 15, 2019; Published online: October 25, 2019 How to cite this article: Todorović L, Mandušić V, Vučetić Tadić B, Živaljević V, Paunović I, Stanojević B.Altered expression of microRNA-30a-3p in papillary thyroid cancer and its association with clinicopathological characteristics. Arch Biol Sci. 2020;72(1):31-6.